IPNU IPPNU’S LIFE SKILLS EDUCATIONS EFFORTS IN DEVELOPING CRITICAL THINKING, CREATIVITY, COLLABORATION, COMMUNICATION OF STUDENTS AT MTS MA’ARIF AR-RIDHO WONOSOBO - Nur Kuningaisatun Silmi; Faisal Kamal; Ali Imron (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
This study aims to analyze the Life Skills education efforts implemented by IPNU IPPNU to develop critical thinking, creativity, collaboration, and communication skills in students at MTs Ma'arif Ar-Ridho Wonosobo. This study used a qualitative approach with descriptive methods, using data collection techniques such as observation, interviews, and documentation. The results indicate that various programs and activities organized by IPNU IPPNU, such as leadership training, discussion forums, social activities, and the development of interests and talents, significantly contribute to improving students' 4C competencies: Critical Thinking, Creativity, Collaboration, and Communication. Students' critical thinking skills develop through discussions and studies, creativity grows through innovative and productive activities, collaboration is fostered through group activities, and communication skills are enhanced through public speaking practice and active participation in organizations. Thus, the Life Skills education implemented by IPNU IPPNU has proven to be a powerful complement to formal education in developing students who are active, confident, and possess 21st-century skills. This study recommends that these programs continue to be developed sustainably to improve the quality of students' human resources